Agroecological initiatives in the Mekong Region: a systematic literature review and mapping reveals their implications for transitioning to sustainable food systems - Hett C; Aye ZC; Gironde C; Beban A; Castella J-C; Bernhard R; Ehrensperger A (Taylor and Francis Group, 2023)
In the Mekong Region, agroecological approaches provide a niche alternative to the dominant traditional or intensive farming systems. We conducted a synthesis of current evidence on agroecological interventions by means of a systematic literature review and mapping of case studies in Cambodia, Vietnam, Laos, Thailand, and Myanmar. The majority of the 271 identified cases focussed on practical and technical support. Interventions using holistic approaches, and such that focused on improving food systems through innovative territorial governance, value chain arrangements, and policy frameworks were scarce. Most cases targeted the agroecological optimization and the modernization of traditional farming systems. A mere 18 of our cases addressed gender in relation to agroecology. To scale agroecological transitions, sectoral barriers have to be overcome. There is an urgent need to put a pronounced focus on the diversification of ecosystem services in commercial agriculture and degraded areas and on women’s contributions to sustainable farming.
Keywords: Agroecology initiatives; spatial inventory; Mekong region; ecosystem services; gender relations; agroecological transitions